2021
DOI: 10.1016/j.celrep.2021.109561
|View full text |Cite
|
Sign up to set email alerts
|

Rapid selection of HIV envelopes that bind to neutralizing antibody B cell lineage members with functional improbable mutations

Abstract: Highlights d Few naturally acquired mutations are required for the function of HIV bnAb DH270.6 d Acquired improbable mutations are critical for neutralization d Immunogens to elicit lineage Abs containing key DH270.6 mutations are identified d More probable evolution pathways to induce DH270.6-like bnAbs likely exist

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 62 publications
(116 reference statements)
1
20
0
Order By: Relevance
“…HIV-1 bNAbs obtain a large number of somatic mutations, but not all mutations are functionally important. B cells evolve by positive selection to identify boosting candidate immunogens ( Swanson et al., 2021 ). In line with previous observations from viremic controllers or elite controllers ( Freund et al., 2017 ; Kumar et al., 2019 ), we observed that autologous plasmas can potently neutralize viruses not only from earlier time points but also from concurrent and later time points.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 bNAbs obtain a large number of somatic mutations, but not all mutations are functionally important. B cells evolve by positive selection to identify boosting candidate immunogens ( Swanson et al., 2021 ). In line with previous observations from viremic controllers or elite controllers ( Freund et al., 2017 ; Kumar et al., 2019 ), we observed that autologous plasmas can potently neutralize viruses not only from earlier time points but also from concurrent and later time points.…”
Section: Discussionmentioning
confidence: 99%
“…For vaccine types that do not rely on viral replication, Env immunogens would need to contain a shorter V1V2 loop and lack the N413 glycan to expand the desired DH270-like bnAb precursors. Then, Envs that could elicit improbable mutations in DH270-lineage members, as described elsewhere, would be used ( 16 , 17 , 29 ). This regimen would be analogous to the prime-boost regimens previously used for the CH103 and CH235 cooperating bnAb lineages, for which structural investigations guided the development of immunogens that elicited long-lasting antibody responses in macaques ( 12 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar mutations occur in the I2 intermediate, most notably an F101C mutation spatially adjacent to the LCDR3 base that results in the formation of an additional disulfide bond in the antibody between residues 91 and 101 (Supplemental Figure 9D). This mutation is among the previously described minimal set of mutations needed to reach ~90% of DH270.6 breadth 29 . A considerable number of mutations in and affecting LDCR3 were also a part of the minDH270 construct and have distinct effects on epitope interaction in the I2 intermediate bound structure.…”
Section: Maturation After I3: a Complex Series Of Mutations In I2 Res...mentioning
confidence: 99%
“…Particles were picked automatically using a Gaussian disk of 80 Å in radius as the search template. All the picked particles were extracted with box size of 384 pixels and down scaled to 192 pixels (binning 2) and subjected to 8 rounds of refinement in cisTEM 29 , using an ab-initio model generated with cryoSPARC 26 . The distribution of scores assigned to each particle by cisTEM showed a clear bi-modal distribution and only particles in the group containing the higher scores were selected for further processing.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation